Implementation Evaluation of Steering Teens Safe: Engaging Parents to Deliver a New Parent-Based Teen Driving Intervention to Their Teens. (August 2013) - Ramirez, Marizen; Yang, Jingzhen; Young, Tracy; Roth, Lisa; Garinger, Anne; Snetselaar, Linda; Peek-Asa, Corinne
Parents play a fundamental role in teaching their children safe driving skills to reduce risk of motor vehicle crashes, the leading cause of death for teens. Steering Teens Safe is a new parent-based intervention that equips parents with communication skills to talk about, demonstrate, and practice safe driving behaviors and skills with their teens. This implementation evaluation focuses on a sample of 83 parents who delivered Steering Teens Safe to their teens. One-, 2- and 3-month follow-up assessments were conducted with intervention parents to evaluate the self-reported quantity and quality of talking about, demonstrating, and practicing safe driving goals with teens; perceived success and benefit of the program; and barriers to implementation. Over 3 months of follow-up, parents discussed driving goals with their teens for a median of 101.5 minutes. The most frequently addressed topics were general safety principles, including distracted driving, driving in bad weather, wearing a seat belt, and being a safe passenger. Parents spent a median of 30 minutes practicing safe driving skills such as changing lanes. Sixty-seven percent of parents talked to their children about rural road safety, but just 36% demonstrated and half practiced these skills with their teens. Barriers to implementation include time and opportunity barriers and resistant attitudes of their teens. However, barriers neither affected frequency of engagement nor parents' perceived benefit and comfort in delivering the program. Parents with time/opportunity barriers also had higher practice and demonstration times than parents without these barriers. Findings indicate high acceptability among parent implementers and promise for real-world delivery. Future studies are needed to assess intervention impact.